The Effect Of Drinking Water On Hyperglycemia In Diabetes Mellitus - Jenny Saherna; Erhasmi Rezkiawan (Health Media, 2020)
Drinking water is needed for the body and plays an active role in the hydrolysis process, a major process in digestion. Regularly consuming water, helps as a solvent for nutrients in the form of monosaccharides, amino acids, fats, vitamins, minerals as well as oxygen and hormones, all of which are carried to all cells in need. The benefits of consuming water regularly are very good for the body because it functions as a solvent to transport the rest of the metabolism, carbon dioxide, urea and excess glucose in the body due to the inability of the pancreas to produce insulin, so that blood sugar levels increase (hyperglycemia), this is one of the causes. signs of diabetes mellitus. This study aims to examine the effect of drinking water on hyperglycemia in diabetes mellitus. This study aims to examine the effect of drinking water on hyperglycemia in diabetes mellitus. This study used a pre-experimental design with a static group comparation design, using accidental sampling technique, statistical analysis of paired t test and independent sample t test with a significant value of α <0.05. The results of the study, there was a significant difference in the level of blood sugar levels in the intervention group with the control group. Conclusion, drinking water regularly and in accordance with regulatory limits, will help physiologically reduce blood glucose levels in addition to getting insulin therapy.